Sixteen diverse laboratory mouse reference genomes define strain-specific haplotypes and novel functional loci. (November 2018) - Lilue, Jingtao; Doran, Anthony; Fiddes, Ian; Abrudan, Monica; Armstrong, Joel; Bennett, Ruth; Chow, William; Collins, Joanna; Collins, Stephan; Czechanski, Anne; Danecek, Petr; Diekhans, Mark; et al.
Abstract We report full-length draft de novo genome assemblies for 16 widely used inbred mouse strains and find extensive strain-specific haplotype variation. We identify and characterize 2, 567 regions on the current mouse reference genome exhibiting the greatest sequence diversity. These regions are enriched for genes involved in pathogen defence and immunity and exhibit enrichment of transposable elements and signatures of recent retrotransposition events. Combinations of alleles and genes unique to an individual strain are commonly observed at these loci, reflecting distinct strain phenotypes. We used these genomes to improve the mouse reference genome, resulting in the completion of 10 new gene structures. Also, 62 new coding loci were added to the reference genome annotation. These genomes identified a large, previously unannotated, gene (Efcab3-like ) encoding 5, 874 amino acids. MutantEfcab3-like mice display anomalies in multiple brain regions, suggesting a possible role for this gene in the regulation of brain development. Sequence assemblies for the genomes of 16 widely used inbred laboratory mouse strains highlight considerable strain-specific haplotype variation and allow for the identification of regions with the greatest sequence diversity between strains.